Inclusión de harina de tuza de maíz y bicarbonato de sodio en alimentación de ponedoras y su efecto en los parámetros productivos - Alcívar Mendieta, Harold Francisco (2019)
The investigation consisted in evaluating the inclusion of two levels of corn husk and two levels of sodium bicarbonate in feed of laying hens of 85 weeks on the productive parameters. A completely randomized design was used, the treatments evaluated were control formula (T0), 1.5% tuza +190 mEq / kg (T1), 1.5 + 200mEq / kg (T2) 3.0% + 190mEq / kg (T3) and 3.0% + 200MmEq / Kg (T4). The data was analyzed by ANOVA and Tukey test with the statistical package InfoStat. The highest weekly weight was T0 with 2.2 ± 0.04 kg. The lowest consumption was found in T4 with 0.10 ± 0.0009 kg, also achieved the highest percentage of production with 80.6% and obtained a shell thickness of 0.44mm. In the feed conversion the T1 obtained the lowest average with 2.00 ± 0.018 kg, was the highest egg weight with 67.9g, an accumulated egg mass of 1.81kg, obtained a shell coloration of 90, in what concerns eggs accumulated per hen obtained 26.87 eggs per week and the average pH was 6.9 almost neutral. The highest consumption of egg food was T3 with 165.35gr / y, and yolk pigmentation was 12 (d.s.m.), T2 with 1.95% was the lowest percentage of broken eggs. The highest cost benefit was T0 and T1 ($1.10), followed by T2, T3 and T4 respectively ($1.09). The inclusión of corn gum and baking soda does not influence the productive parameters of laying hens.